Closed-shell paramagnetic porphyrinoids. Issue 71 (21st August 2017) - Valiev, Rashid R.; Fliegl, Heike; Sundholm, Dage
Abstract : Magnetizabilities and magnetically induced ring-current strength susceptibilities have been calculated at the Hartree–Fock, density functional theory and second order Møller–Plesset levels for a number of antiaromatic closed-shell carbaporphyrins, carbathiaporphyrins and isophlorins. Abstract : Magnetizabilities and magnetically induced ring-current strength susceptibilities have been calculated at the Hartree–Fock, density functional theory and second order Møller–Plesset levels for a number of antiaromatic closed-shell carbaporphyrins, carbathiaporphyrins and isophlorins. The calculations yield a linear relation between magnetizabilities and ring-current strength susceptibilities. The calculations show that the porphyrinoids with the largest ring-current strength susceptibility are closed-shell paramagnetic molecules with positive magnetizabilities. The closed-shell paramagnetism is due to the large paramagnetic contribution to the magnetizability originating from the strong paratropic ring current in the antiaromatic porphyrinoids.